Can compression assist with ankle movement preparation? A comparison of static, dynamic, and dynamic with compression stretching on ankle dorsiflexion motion - Hagen, N. D.; Reyes, C.; Liu, E. K. (Journal of Australian Strength and Conditioning, 2017)
A lack of ankle range of motion (ROM) can affect gross movement patterns (21). It is unclear which ankle mobilization technique has the greatest influence on ankle function, specific to an ankle warm-up strategy. The purpose of this study was to compare warm-up methods of dynamic stretching, static stretching, and dynamic stretching with compression on ankle dorsiflexion (DF) ROM. Thirty-two subjects (20 males, 12 females; 22.1 ± 2.4 years;) were randomly assigned to one of 4 treatment groups: a control group of no treatment (CTRL), closed-chain ankle DF dynamic stretching (DYN), closed-chain ankle DF static stretching (STAT), and closed-chain ankle (CKC) DF dynamic stretching with compression (BAND). The dependent variables consisted of closed-chain ankle DF lunge test, seated open-chain (OKC) ankle DF goniometry, and a bodyweight overhead squat test. Each dependent variable was tested before and immediately post-treatment and then every four minutes for the next 12 minutes. Both the BAND and DYN group lead to significant changes in OKC and CKC outcomes (p< 0.05). The BAND group was the only group that had a significant change in squat outcomes (p < 0.05). The results of this study provide inconclusive evidence of the efficacy of compression bands during ankle mobilizations. The outcome of this randomized controlled trial supports the use of both active closed-chain DF stretching with and without compression as components of movement preparation. If the goal is to improve squat function, then the application of compression based self-mobilization was optimal.